Pest Infestation of Dipterocarpus retusus (Blume) Fruit at Different Heights in KPHP BATULANTEH - yosephin nugraheni; Tati Suharti; Septiantina Riendriasari (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2021)
Keruing gunung (Dipterocarpus retusus) is a non-timber forest product (NTFP) as a fruit producer that can be used as raw material for vegetable fats. One of the problems faced in planting programs for both production and conservation forests is the presence of fruit pests. The purpose of this study was to determine the fruit pests infestation fruits of D. retusus and the effect of altitude on fruit size and weight in Batulanteh Sumbawa. Fruit samples were collected at locations with different heights, namely below 1000 masl (T 22ºC, RH 83%) and above 1000 masl (T 20ºC, RH 88%). The samples of invading pests were observed and measured morphometry and morphology. The results showed that the insect infestation on the fruit was Alcidodes crassus. The percentage of fruit severity level reached more than 50% at each location. Elevation has a significant effect on fruit diameter and fruit weight, both infested by pests and whole fruit.